2016
DOI: 10.1097/md.0000000000005411
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatry outpatient visits by atopic dermatitis patients varying in the complexity of their prescriptions

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Anxiety disorders have been associated with AD in register studies (Table I), and anxiety was the third most common psychiatric comorbidity in AD patients in our study. Our findings are comparable to studies from the United States (7) and South Korea (6), which reported that patients with AD are twice as likely to have an anxiety disorder as healthy individuals. In contrast to other register study findings and our results, the recent Danish register study (8) found that moderate-to-severe AD was associated with an increased risk of antidepressant and anxiolytic medication use, but not with depression or anxiety.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Anxiety disorders have been associated with AD in register studies (Table I), and anxiety was the third most common psychiatric comorbidity in AD patients in our study. Our findings are comparable to studies from the United States (7) and South Korea (6), which reported that patients with AD are twice as likely to have an anxiety disorder as healthy individuals. In contrast to other register study findings and our results, the recent Danish register study (8) found that moderate-to-severe AD was associated with an increased risk of antidepressant and anxiolytic medication use, but not with depression or anxiety.…”
Section: Discussionsupporting
confidence: 87%
“…First author, year n Study design (Country) Comorbidity Data source Schmitt, 2009 (9) 3,769 A regional register study (Germany) Affective; neurotic, stress-related, somatoform; personality and behaviour; schizophrenic disorders GKV database Saxony, interdisciplinary administrative outpatient database from Germany Cheng, 2015 (5) 6,640 A nationwide longitudinal register study (Taiwan) Major depressive disorder, anxiety disorders Taiwan National Health Insurance Research Database Kim, 2015 (12) 1,517 A cross-sectional register study (South Korea) Depression, anxiety, somatization Regional Conscription Register Shin, 2016 (6) 25,419 A nationwide cohort study (South Korea) Psychiatric disorders Korea National Health Insurance Cohort Data Shrestha, 2017 (7) 119,716 A register study from 3 databases (USA) Anxiety, depression, sleep disorders Commercial, Medicare and Medi-Cal databases Egeberg, 2017 (13) 7,937 A nationwide register study (Denmark) Depression, anxiety Danish National Patient Register Thyssen, 2018 (8) 10,038 A register study (Denmark) Depression, anxiety Danish National Patient Register…”
Section: Table I Register Studies About Atopic Dermatitis and Its Psmentioning
confidence: 99%
“…The 2017 estimates do not use current vital statistics due to the lag time in the release of reported data, and the DALY metric for skin diseases does not consider disability from related systemsfor example, mental health comorbidity in atopic dermatitis. [40][41][42][43] Misclassification of disease is possible, particularly when relying on administrative coding of diagnoses. Future iterations of GBD ought to disaggregate DALYs and YLLs attributable to differences in latitude and sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%
“…levels of pro-inflammatory cytokines, disturbance in cholinergic regulation or excessive histamine production (10,44,45) . In fact, high systemic levels of inflammatory mediators produced in the allergic process appears to have an important contribution in limbic system deregulation and depression pathogenesis (46) . On the other hand, there is a robust body of evidence showing altered circulating levels of immune cells and inflammatory mediators in patients with mental disorders.…”
Section: O R R E C T E D P R O O Fmentioning
confidence: 99%